PENGARUH PENJUALAN PRODUK UTAMA TERHADAP PENJUALAN PRODUK SEKUNDER DI FOOTSTEP FOOTWEAR - Bilal Fiisabilillah; Sa'ad Noor (Ekonis: Jurnal Ekonomi dan Bisnis, 2022)
Abstract : This study intends to provide an overview of the effect of the sale of the main product on the sale of secondary products at one of the local brands, Footstep Footwear. The purpose of this research is to find out how the influence of the sale of the main product on the sale of the secondary product and the sale of the main product which has a significant influence on the sale of the secondary product in Footstep Footwear. The research method used in this study is a quantitative descriptive method, which is a method to obtain an overview of the effect of sales of the main product on sales of secondary products, by correlating the sales data of the main product with secondary product data in Footstep Footwear in 2020. The researcher uses the Spearman rank correlation coefficient analysis technique to determine the level of the correlation coefficient between the independent variables, namely sales of primary products and the dependent variable of sales of secondary products. The results indicate that there is a correlation coefficient between sales of primary products and sales of secondary products in Footstep Footwear of r = 0.821 which is classified as very strong and the Determinant Coefficient or the magnitude of the influence of sales of primary products on sales of secondary products is 67.40 %. Based on the results of the study, the researcher concluded that there was an effect of the sale of the main product on the sale of the secondary product in Footstep Footwear. And among the main products, Sneakers Products are Sub. The most significant variable has an effect on secondary product sales in Footstep Footwear.Keyword: Sale, Product, Footstep Footwear